Development of successive cambia and structure of wood in Gallesia integrifolia (Spreng.) Harms (Phytolaccaceae) - Rajput, Kishore Shankersinh [UNESP]; Romeiro, Diego; Longui, Eduardo Luiz [UNESP]; Marcati, Carmen Regina [UNESP] (Springer, 2012)
Stem diameter in Gallesia integrifolia (Spreng.) Harms (Phytolaccaceae) increases by forming concentric rings of xylem alternating with phloem, which show frequent anastomoses. After a period of primary growth and the formation of first (normal) ring of vascular cambium, further successive rings are initiated outside this cambium. The second ring of cambium originates from the pericycle parenchyma located between the proto-phloem, and the pericycle fibres. Each cambium produces centripetally secondary xylem and centrifugally secondary phloem. Differentiation of xylem precedes that of phloem and the first elements formed are always xylem fibres. Structurally, the vascular cylinder is composed by successive rings of secondary xylem and phloem. These rings are separated by wide bands of conjunctive parenchyma tissue. Presence of collateral vascular bundles with irregular orientation is observed in the region of anastomoses of two or more bands of conjunctive tissue. These bundles are surrounded by isodiametric, lignified and thick-walled cells. In some of the cambial rings, occurrence of polycentric rays was also noticed; these rays are tall, and characterized by the presence of meristematic regions that differentiated into thick-walled elements of secondary xylem. Origin and development of the successive cambia and the structure of xylem are discussed.
Keywords: Cambial variant; Gallesia; Phytolaccaceae; Successive cambia